The Health Profile of Students and Teachers in Madrasah Al Ihsan, Kecamatan Ciparay, Kabupaten Bandung - Febrina, Ellin; Herawati, Irma E.; Wahyuni, Indah S.; Rusdianto, Aziiz M.; Hendriani, Rini; Puspitasari, Irma M.; Mutakin, Mutakin; Halimah, Eli; Sumiwi, Sri A.; Levita, Jutti (Universitas Padjadjaran, Indonesia, 2024)
The prevalence of diabetes mellitus and hypertension in Indonesia is increasing both in low- and high-income communities. Therefore, health awareness should be started from a younger age for the prospective future generation. This study, included in a community engagement activity, aims to assess the health profile, in terms of blood pressure (BP) and total cholesterol, of the students (by cross-sectional method) and teachers (by cohort method) of a private madrasah in the rural area of Kecamatan Ciparay, Kabupaten Bandung, West Java. 54 students and 10 teachers participated in this study. Results revealed that the students' average systolic and diastolic BP were 120.23 mmHg and 78.67 mmHg, respectively. The average systolic BP of the teachers in August 2021, January 2022, and August 2022 was 136.8 mmHg, 128.1 mmHg, and 131.9 mmHg, respectively. The average diastolic BP of the teachers in August 2021, January 2022, and August 2022 were 91.6 mmHg, 87.3 mmHg, and 87.1 mmHg, respectively. Moreover, the average cholesterol levels of the students (148.38 mg/dL) and the teachers (190.81 mg/dL) were categorized as normal. Taken together, the health profile of the students and the teachers in Madrasah Al Ihsan is within the normal range. This activity gets positive support from the school and needs sustainability.